Aneurisma de aorta ascendente en paciente con síndrome de Marfan - Nápoles Lizano, Mario E.; Ibáñez Azán, Rafael; Moreno-Martínez, Francisco L.; Ricardo Olivera, Daylín (CorSalud, 2021)
Aneurisma de aorta ascendente en paciente con síndrome de Marfan